New institutional geographies of higher education: The rise of transregional university alliances. (May 2016) - Harrison, John; Smith, Darren P; Kinton, Chloe
This article opens up debates about the deepening uneven geographies of higher education through a critical analysis of transregional university alliances. Focusing on the formation of research consortia and Doctoral Training Centres, we reveal the emergence of over 50 transregional alliances between United Kingdom universities. Despite each consortium operating at a variously defined regional scale there has been no explicit attempt to account for their geographical basis. Providing the first-ever analysis of this unfolding phenomenon, we demonstrate how the rise of transregional alliances is indicative of, and a response to, universities operating in an intensely neoliberalised political economy. Bringing together emergent theories of regionalism with emerging worlds of (neoliberal) higher education, our article reveals how, why and where universities are engaging in more intensively targeted, exclusive approaches to regional development. We argue that higher education is conducive to the weakening of fixed regional territories, and propose the metaphor of 'regional constellations' for interpreting transregional geographies. Finally, our analysis suggests that while high-performing research institutions may compete better by forming consortia, transregional alliances lead to a more unequal and divided university sector.